2012
DOI: 10.3389/fphys.2012.00237
|View full text |Cite
|
Sign up to set email alerts
|

In Search for Factors that Drive Hantavirus Epidemics

Abstract: In Europe, hantaviruses (Bunyaviridae) are small mammal-associated zoonotic and emerging pathogens that can cause hemorrhagic fever with renal syndrome (HFRS). Puumala virus, the main etiological agent carried by the bank vole Myodes glareolus is responsible for a mild form of HFRS while Dobrava virus induces less frequent but more severe cases of HFRS. Since 2000 in Europe, more than 3000 cases of HFRS have been recorded, in average, each year, which is nearly double compared to the previous decade. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 151 publications
(256 reference statements)
2
57
1
Order By: Relevance
“…Some recreational/leisure or work-related activities are known to be risk factors for PUUV infection [36][37][38]; but this was not found in our study. Travel to other endemic countries, such as in Asia or south-east Europe, was also not found to increase risk.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Some recreational/leisure or work-related activities are known to be risk factors for PUUV infection [36][37][38]; but this was not found in our study. Travel to other endemic countries, such as in Asia or south-east Europe, was also not found to increase risk.…”
Section: Discussioncontrasting
confidence: 55%
“…On the basis of prevalence data from a study performed in the north-eastern part of Switzerland in 2002-03, we investigated predominantly young soldiers as a potential risk group, but since their military service did not take place during a year of increased hantavirus activity in regions close to Switzerland, they were not at particular risk of infection [4,27,38]. Due to time-consuming preparatory work, the period of blood collection in the military personnel could not be handled flexibly and could not be postponed to the following year: in that year, increased numbers of hantavirus infections were documented in Germany [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…In Belgium, Linard et al (2007b) found that infected bank voles were common in the parts of the country that had a large proportion of broad-leaved forests. In Germany, habitat structures associated with old forests such as dead wood was linked to increased probability of PUUV in bank voles within homogenous forest landscapes (Heyman et al 2012, Thoma et al 2014. Also, bank voles in wooded recreation areas and forested city parks were found to have high PUUV prevalence (Essbauer et al 2007, Ulrich et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Late frost events in spring may have a significant damaging impact on plants and lead to an economic loss in agriculture [40]. Additionally, late frost is considered to be an abiotic factor triggering tree mast [41], which, in turn, leads to high rodent densities and, subsequently, to Hantavirus epidemics, as observed in temperate Europe [42].…”
Section: Spatial and Temporal Resolutionmentioning
confidence: 99%